Odpowiedzi

2010-04-06T14:54:18+02:00
A)2CH₃COOH + Ca(OH)₂ --> (CH₃COO)₂Ca + 2H₂O
b)2CH₃COO⁻ + 2H⁺ + Ca²⁺ + 2OH⁻ --> 2CH₃COO⁻ + Ca²⁺ + 2H₂O
c)2H⁺ + 2OH⁻ --> 2H₂O /: 2
H⁺ + OH⁻ --> H₂O

a)2HCOOH + Ca(OH)₂ --> (HCOO)₂Ca + 2H₂O
b)2HCOO⁻ + 2H⁺ + Ca²⁺ + 2OH⁻ --> 2HCOO⁻ + Ca²⁺ + 2H₂O
c)2H⁺ + 2OH⁻ --> 2H₂O /: 2
H⁺ + OH⁻ --> H₂O
2010-04-06T14:56:52+02:00
1. a) 2 CH3COOH + Ca(OH)2 -> (CH3COO)2Ca + 2 H2O
b) 2 CH3COO- + 2 H+ + Ca2+ + 2 OH- --> 2 CH3COO- + Ca2+ + 2 H2O
c) 2H+ + 2OH- --> 2H2O
H+ + OH- --> H2O

2. a) 2 HCOOH + Ca(OH)2 -> (HCOO)2Ca + 2 H2O
b) 2 HCOO- + 2H+ + Ca2+ + 2 OH- --> 2 HCOO- + Ca2+ + 2 H2O
c) 2H+ + 2OH- --> 2H2O
H+ + OH- --> H2O